1988
DOI: 10.1017/s004317450007586x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Red Rice (Oryza sativa) Seed Production with Fluazifop and Quizalofop

Abstract: Field research was conducted in 1985 and 1986 to compare the efficacy of fluazifop and quizalofop on production of panicles and seeds of red rice. Single and first sequential treatments were applied to red rice in the early-tillering, midtillering, and panicle initiation stages of growth. Sequential treatments were applied 14 days after each earlier application to red rice in the midtillering, late-tillering, and early-heading growth stages, respectively. Both herbicides were applied singly or sequentially at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Chlorosis and eventual necrosis develop 1 to 3 wks after application (Ahrens 1994). Research has shown that quizalofop is effective in controlling both barnyardgrass (Noldin et al 1998) and red rice (Salzman et al 1988). In soybean, quizalofop is applied at from 35 to 84 g ai ha –1 (Shaner 2014), but labeled use rates in quizalofop-resistant rice could be as high as 138 g ha –1 for single application (Anonymous 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorosis and eventual necrosis develop 1 to 3 wks after application (Ahrens 1994). Research has shown that quizalofop is effective in controlling both barnyardgrass (Noldin et al 1998) and red rice (Salzman et al 1988). In soybean, quizalofop is applied at from 35 to 84 g ai ha –1 (Shaner 2014), but labeled use rates in quizalofop-resistant rice could be as high as 138 g ha –1 for single application (Anonymous 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Red rice control from single applications of many selective grass herbicides is often inconsistent (Khodayari et al 1987;Salzman et al 1989). In most cases, consistency and increased control were achieved with sequential herbicide applications (Barrentine et al 1984;Salzman et al 1988;). a Data are averages of responses from five separate herbicide treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Adequate moisture for red rice growth and reproduction is important in upland nonirrigated environments. Moisture stress affects seedhead development of red rice and domestic rice (De Datta 1981;Salzman et al 1988Salzman et al , 1989.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herbicide applications that do not kill plants may also reduce seed production. Sublethal doses of herbicide reduced seed production of several weed species by as much as 90% (Biniak and Aldrich, 1986;Salzman, Smith, and Talbert, 1988). Although seed production in most weed species can be reduced by management factors, seed production will likely be adequate, even with moderate weed infestations, to allow rapid increases in the seed bank (Schweizer and Zimdahl, 1984;Hartzler, 1996).…”
Section: Additions To the Seed Batikmentioning
confidence: 99%